Cytotoxic peptides with insulin‐releasing activities from skin secretions of the Italian stream frog Rana italica (Ranidae). (11th July 2017) - Conlon, J. Michael; Musale, Vishal; Attoub, Samir; Mangoni, Maria Luisa; Leprince, Jérôme; Coquet, Laurent; Jouenne, Thierry; Abdel‐Wahab, Yasser H. A.; Flatt, Peter R.; Rinaldi, Andrea C.
Abstract : Peptidomic analysis of norepinephrine‐stimulated skin secretions from Italian stream frog Rana italica led to the purification and characterization of two host‐defense peptides differing by a single amino acid residue belonging to the brevinin‐1 family (brevinin‐1ITa and ‐1ITb), a peptide belonging to the temporin family (temporin‐ITa) and a component identified as prokineticin Bv8. The secretions contained relatively high concentrations of the methionine‐sulphoxide forms of brevinin‐1ITa and ‐1ITb suggesting that these peptides may have a role as antioxidants in the skin of this montane frog. Brevinin‐1ITa (IVPFLLGMVPKLVCLITKKC) displayed potent cytotoxicity against non‐small cell lung adenocarcinoma A549 cells (LC50  = 18 μM), breast adenocarcinoma MDA‐MB‐231 cells (LC50  = 8 μM) and colorectal adenocarcinoma HT‐29 cells (LC50  = 18 μM), but the peptide was also strongly hemolytic against mouse erythrocytes (LC50  = 7 μM). Temporin‐ITa (VFLGAIAQALTSLLGKL.NH2 ) was between three and fivefold less potent against these cells. Brevinin‐1ITa inhibited growth of both Gram‐positive Staphylococcus epidermidis and Gram‐negative Escherichia coli as well as a strain of the opportunist yeast pathogen Candida parapsilosis, whereas temporin‐ITa was active only against S. epidermidis and C. parapsilosis . Both peptides stimulated the release of insulin from BRIN‐BD11 clonal β‐cells at concentrations ≥1 nM, but brevinin‐1ITa was cytotoxic to the cells at concentrations ≥3 μM. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Peptidomic analysis of secretions from the Italian stream frog Rana italica led to the purification and characterization of brevinin 1ITa and 1ITb together with their methionine‐sulfoxide forms, temporin ITa and prokineticin Bv8. Brevinin 1ITa displayed potent cytotoxicity against a range of tumor cell lines and broad‐spectrum antimicrobial activity but was strongly hemolytic. Both brevinin 1ITa and temporin ITa stimulated the release of insulin from BRIN‐BD11 clonal β‐cells at concentrations ≥1 nM, but brevinin 1ITa was cytotoxic to the cells at concentrations ≥3 μM.